2023
DOI: 10.3390/ijerph20032507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Green Network Management of Urban Street Trees on Airborne Particulate Matter (PM2.5) Concentration

Abstract: Street trees are crucial for air pollutant reduction in urban areas. Herein, we used computational fluid dynamics (CFD) simulation to identify changes in airborne particulate matter (PM2.5) concentration based on wind characteristics (direction and velocity) and the green network of street trees. The green network was assessed based on composition of the green area of street trees in the central reserve area and between the motor and pedestrian roads. The PM2.5 concentration varied according to the presence or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…We planted roadside trees in a multi-planting structure with both arbors and shrubs to enhance pollutant dispersal. 54 Design parameters for roadside barriers were optimized to maximize pollution capture and dispersion with large trees in the back and smaller trees or shrubs in front. For each area, we targeted a wide distribution of species; considering sun exposure, soil type, disease, hydrology, community preference, aesthetics, and plant availability and suitability of the space for planting trees.…”
Section: Methodsmentioning
confidence: 99%
“…We planted roadside trees in a multi-planting structure with both arbors and shrubs to enhance pollutant dispersal. 54 Design parameters for roadside barriers were optimized to maximize pollution capture and dispersion with large trees in the back and smaller trees or shrubs in front. For each area, we targeted a wide distribution of species; considering sun exposure, soil type, disease, hydrology, community preference, aesthetics, and plant availability and suitability of the space for planting trees.…”
Section: Methodsmentioning
confidence: 99%
“…The calibration of these sensors should be performed for each measurement and ideally compared with data from monitoring stations. [17][18][19][20][21][22][23][24][25][26] Monitoring stations…”
Section: Validation Methodsmentioning
confidence: 99%
“…In addition, promoting walking can lower obesity rates and enhance academic performance [43]. It can also help older adults maintain physical function and independence to decrease the risk of falls [24] and improve the quality of life through urban trees [44] and healthy lifestyles by incorporating nature into healthcare strategies [45].…”
Section: Research Backgroundmentioning
confidence: 99%
“…These ideas are consistent with innovative growth principles emphasizing the importance of healthy streets and environmental performance measures. The results conducted by Yu et al [96] and Jeong et al [44] suggested green networks for reducing air pollution, while Velázquez et al [97] recommended controlling extreme climatic conditions by incorporating vegetation areas with trees to minimize sun exposure. Kent et al [12] considered the interaction of urban form-related walkability and health interaction, while Shartova et al [17] proposed expanding green infrastructure and urban form implementation.…”
Section: Comparison With Prior Studiesmentioning
confidence: 99%
See 1 more Smart Citation